A one-pot, three-component, solvent-free synthesis of novel 6H-chromeno[3', 4':5, 6]pyrido[2, 3-d]pyrimidine-triones under microwave irradiation. (1st December 2018) - Firoozpour, Loghman; Yahyavi, Hoda; Ejtemaei, Ramona; Moghimi, Setareh; Foroumadi, Alireza
A green and efficient method for preparing novel heterocyclic systems is established through the reaction of differently substituted benzaldehydes, barbituric acid and 4-amino-2H-chromene-2-one under solvent-free conditions. This method affords 6H-chromeno[3', 4':5, 6] pyrido[2, 3-d]pyrimidine-trione derivatives in high yields and short reaction times.